آفات القلب الولادية لدى مراجعي مشفى الأسد الجامعي باللاذقية - سليمان سليمان علي (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم الأطفال _ مشفى الأسد الجامعي جامعة تشرين وامتدت من حزيران 2007 وحتى آب 2010 تم دراسة (487) طفل (216 ذكر و 271 أنثى)، وقد تبين من الدراسة أن أكثر تشوهات القلب مصادفة في منطقتنا هي الفتحات ما بين البطينين (VSDs) تلاها مباشرة الفتحات ما بين الأذينين (ASDs) فبقاء القناة الشريانية (PDA) فتضيق الشريان الرئوي (PS) فتشوه الوسادة (AVSD) فرباعي فالو, فتضيق برزخ الأبهر وتبادل منشأ الأوعية الكبرى (COA و D- TGA). وقد تبين أيضاً أن هناك عوامل أخرى مثل الجنس والعرق وعوامل بيئية, وراثية, ماسخة وصبغية مؤثرة وأن تناذر داون هو الاضطراب الصيغي الأكثر مشاركة. Between June 2007 and August 2010, 487 children (216 males and 271 females) with Congenital heart disease (CHD) were examined and traced in the Pediatric Department , University A-Assad Hospital, Tishreen University. Ventricular Septal Defect (VSD) was the commonest anomaly, followed in descending order of frequency by arterial septal defect (ASD), Patent ductus arteriouscs (PDA), Pulmonary Stenosis (PS), AV-canal septal defect (AVSD), tetrology of fallot (TOF), coarctation of the aorta (COA), and the transposition of the great arteries (D-TGA). There are genetic, environmental, sex, ethnic, and chromosomal factors which influence the type and distribution of (CHD). However, Down Syndrome was the commonest associated cause.